Construction of a YAC contig spanning the Xq13.3 subband. - Villard, L; Gecz, J; Colleaux, L; Lossi, A; Chelly, J; Ishikawa-Brush, Y; Monaco, A; Fontes, M (1995)
The loci involved in several X-linked mental retardation syndromes have been linked to the pericentromeric region of the X chromosome long arm (Xq12-q21). To isolate candidate genes for these diseases, we set up the construction of YAC contigs spanning this region. Two of these syndromes (the Juberg-Marsidi syndrome and the alpha-thalessemia mental retardation syndrome) have been recently linked, with high lod scores, to polymorphic probes previously assigned to Xq13.3. We therefore constructed a first YAC contig, encompassing this band, from DXS441 to PGK1. The physical map, deduced from the isolated clones, extends over 2.1 Mb of genomic DNA. Restriction analysis of the YAC contig allowed us to map precisely the loci previously assigned to that chromosomal region and to define their relative order. The validity of this physical map has been checked by comparing Sfi I digests of the YACs to genomic fragments obtained with the same enzyme. A cDNA selection approach, already performed with a previous partial contig, has been extended to cover the whole region.